Operation performance measurement of public rental housing delivery by PPPS with fuzzy-AHP comprehensive evaluation - Yuan, Jingfeng; Li, Wei; Xia, Bo; Chen, Yuan; Skibniewski, Mirosław J. (International Journal of Strategic Property Management, 2019)
As governments promote greatly the Public Private Partnerships (PPPs) to develop the Public Rental Housing (PRH) projects, the effective and efficient operation performance measurement should be pivotal for ensuring the success and sustainable development of these projects. Thus, this paper investigated operation performance indicators (OPIs) and measured the performance level of PRH PPP projects by fuzzy-analytic hierarchy process (AHP) comprehensive evaluation (FACE) method. Four important aspects of PRH PPP projects related to the operation performance and an evaluation indicator system of 21 OPIs from these four aspects were developed, the weights of which were calculated by using the AHP method. Based on fuzzy mathematics and the expert evaluation method, all the OPIs were quantitatively graded according to five ranks of evaluation criteria. Membership functions, weights of OPIs, and maximum membership degree principle were utilized to establish a multi-level FACE model for operation performance measurement of PRH PPP projects. One PRH PPP project of Nanjing, Jiangsu Province in China was chosen as the case study. Evaluation results were derived from the proposed model, and they generally conform to the actual situation. This study provides an effective operation performance measurement framework for PRH PPPs projects.